Restless legs syndrome and post polio syndrome: a case−control study. (13th November 2014) - Romigi, A.; Pierantozzi, M.; Placidi, F.; Evangelista, E.; Albanese, M.; Liguori, C.; Nazzaro, M.; Risina, B. U.; Simonelli, V.; Izzi, F.; Mercuri, N. B.; Desiato, M. T.
<x xml:space="preserve">Abstract</x> Background and purpose The aim was to investigate the prevalence of restless legs syndrome (RLS), fatigue and daytime sleepiness in a large cohort of patients affected by post polio syndrome (PPS) and their impact on patient health‐related quality of life (HRQoL) compared with healthy subjects. Methods PPS patients were evaluated by means of the Stanford Sleepiness Scale and the Fatigue Severity Scale (FSS). The Short Form Health Survey (SF‐36) questionnaire was utilized to assess HRQoL in PPS. RLS was diagnosed when standard criteria were met. Age and sex matched healthy controls were recruited amongst spouses or friends of PPS subjects. Results A total of 66 PPS patients and 80 healthy controls were enrolled in the study. A significantly higher prevalence of RLS (P < 0.0005; odds ratio 21.5; 95% confidence interval 8.17–57) was found in PPS patients (PPS/RLS+ 63.6%) than in healthy controls (7.5%). The FSS score was higher in PPS/RLS+ than in PPS/RLS− patients (P = 0.03). A significant decrease of SF‐36 scores, including the physical function (P = 0.001), physical role (P = 0.0001) and bodily pain (P = 0.03) domains, was found in PPS/RLS+ versus PPS/RLS− patients. Finally, it was found that PPS/RLS+ showed a significant correlation between International Restless Legs Scale score and FSS (P < 0.0001), as well as between International Restless Legs Scale score and most of the SF‐36 items (physical role P = 0.0018, general health P = 0.0009, vitality P = 0.0022, social functioning P = 0.002, role emotional P = 0.0019, and mental health P = 0.0003). Conclusion Our findings demonstrate a high prevalence of RLS in PPS, and that RLS occurrence may significantly influence the HRQoL and fatigue of PPS patients. A hypothetical link between neuroanatomical and inflammatory mechanisms in RLS and PPS is suggested.